Phytochemical screening and usability of weed extracts with antifungal property against rice blast fungus / Siti Nuraisyah Farhana Baharudin - Baharudin, Siti Nuraisyah Farhana (Faculty of Plantation and Agrotechnology, 2018)
Rice blast disease caused by fungus Magnaporthe oryzae is an important and serious disease of rice (Oryza sativa L) in worldwide. This study investigated the phytochemical constituents and antifungal properties of Chromolaena odorata, Ageratum conyzoides and Tetracera indica, respectively against pathogenic fungus of blast disease in paddy plant. Studies were conducted to determine the effect of aqueous weed extracts of Tetracera indica, Ageratum conyzoides and Chromolaena odorata for control of rice blast disease in vitro and in vivo studies. The efficacy of the plant extracts tested against blast pathogen at 100% concentration. In vitro application of the extracts showed that Chromolaena odorata had high fungitoxic effect which controlled the growth of Magnaporthe oryzae with 45.06% inhibition. Ageratum conyzoides extract also showed moderate retardation among those 3 weed extracts tested toward mycelial growth of blast fungus which was about 24.13% of inhibition rate. Although Tetracera indica extract could decrease the mycelial growth of the fungus, it was not as effective as Chromolaena odorata since at 0.13g/ml it only shown17.44% inhibition rate against M. oryzae. Phytochemical analysis for all weed extracts used revealed the presence of secondary metabolic such as alkaloids, glycosides, saponins, tannins and flavonoids. The in vivo study has shown the presence of these active ingredients in the weed extracts which expected responsible for their antifungal properties. The two highest effective weed extracts were Chromolaena odorata and Ageratum conyzoides in vitro srudies. In contrast, in vivo studies showed that both were ineffective to managed blast disease on paddy seedling.